Expansão dos condomínios horizontais e loteamentos fechados em São José do Rio Preto - SP - Barroso, Luiz Fernando de Lemos (2008)
In the last fifty years there has been a high exodus rural in Bazil and from the last decades of the last century are witnessing the exodus urban classes of the better income out of the center, seeking enclosed spaces, which seek to protect and isolate whether the unwanted (violence, poverty, insecurity etc), creating private island of privileges. This research aim is to study the dynamics of production and expansion of gated communities, having as a study case the city of São José do Rio Preto, which presents a dynamic of vertiginous growth of gated communities in their urban area (48 gated communities). The main is to study the production of the businesses, understand their origins, evolution, causal relationship of that production and analyze the specific laws.